POPULASI KUMBANG PENYERBUK Elaeidobius kamerunicus Faust. PADA TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq) - Asmawati Asmawati; Ahmad Ahmad; Kafrawi Kafrawi (Jurusan Budidaya Tanaman Perkebunan, Politeknik Pertanian Negeri Pangkajene Kepulauan, 2019)
Elaeidobius kamerunicus Faust is a beetle that assist the pollination in oil palm flowers; therefore, the number of fruit sets of oil palm relates to the population of E. kamerunicus on a plantation. To determine a correlation between the population of E. kamerunicus Faust with age of oil palm and factors influencing the beetle population, a field study was conducted at PT Nusa Indah Kalimantan Plantations Estate Masalap. Samples were collected from each one block of the oil palm field grown (block) that planted in 2009, 2010 and 2011 using purposive sampling method. There were three anthesis and post-anthesis male flowers were collected from each block. The results of the investigate showed that the highest average of spikelet per plant (104.5) was found at the block of 2009 planting season, hence the population of the pollination insects was more abundant at this block compare to the other two blocks. Total population of the insects at the oldest oil palms was 3959.51 imago on anthesis male flowers and 7674.48 larva on post-anthesis flowers. To summarize the main findings, the population of E. kamerunicus Faust at the oil palm plantation was influenced by plant age, number of spikelet and bloom period of male flowers.